Why are Canadian Judges Drafting Labour Codes - And Constitutionalizing the Wagner Act Model Commentary on Cases, Legislation and Policy [comment] - Langille, Brian (Canadian Labour & Employment Law Journal, 2009)
Judges in Canada now adhere to the view that it is their task to draft labour codes for Canadians - a position recently and fully embraced by the Ontario Court of Appeal in Fraser v. Ontario (Attorney General).' Some commentators believe this is a sound legal development. Others are equivocal. I think it is a very serious mistake. Given the alternatives, it is a strange and undesirable turn of legal events. But the strangeness does not end with the mere fact that we now live with what I call a "judicial labour code" (JLC). There is more. Judges undertaking this exercise, enthusiastically but nonetheless disconcertingly, insist that their nascent labour code happens to contain most of the provisions inserted over the years by Canadian legis- lators in an overtly political effort to "balance" or (in Paul Weiler's term) to "reconcile" the interests of labour and capital. Those provisions relate, for example, to the duty to bargain, to unfair labour. --Introduction